Native American representations : first encounters, distorted images, and literary appropriations - Bataille, Gretchen M., 1944- (University of Nebraska Press, 2001)
In Native American Representations, leading national and international critics of Native literature and culture examine images in a wide range of media from a variety of perspectives to show how depictions and distortions have reflected and shaped cross-cultural exchanges from the arrival of Europeans to today. Focusing on issues of translation, European and American perceptions of land and landscape, teaching approaches, and transatlantic encounters, the authors explore problems of appropriation and advocacy, of cultural sovereignty and respect for the "authentic" text. Most significantly, they ask the reader to consider the question: "Who controls the representation?"